Analisa Fundamental Makro, Fundamental Mikro, Kinerja Keuangan, Kepemilikan Perusahaan, DAR berpengaruh Nilai Perusahaan dengan Struktur Kepemilikan Sebagai Indikator Moderating Pada Perusahaan Food and Beverage yang Terdaftar Pada Bursa Efek Indonesia - Devina Shava Amalia; Hwihanus Hwihanus (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
The purpose of this study was to determine the effect of macro fundamentals, micro fundamentals, financial performance, and company ownership on the value of companies with state ownership structures listed on the Indonesia Stock Exchange in 20219 to 2023. This research uses a quantitative descriptive approach using secondary data for independent and dependent variables. Data is obtained from financial reports, annual reports, and various online platforms including the Indonesia Stock Exchange website. This research targets all state-owned companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, with six companies selected using the random sampling method. The results of hypothesis testing show that one independent variable has a significant influence on the dependent variable, while the other eight variables do not have a significant influence on firm value.